ANTI-INFLAMMATORY ACTIVITY OF CALCIUM CHANNEL BLOCKERS: Pharmaceutical Science-Pharmacology - KOTHIYAL, GITANJALI; B.GUPTA; THAWANI, VIJAY (International Journal of Life Science and Pharma Research, 2012)
Objective: To explore the anti-inflammatory activity of calcium channel blockers. Material and Methods: The anti-inflammatory activity was determined by producing inflammation in rats of either sex. Acute inflammation was produced by injecting carrageenan, formalin and histamine in hindpaw of rats. For sub-acute inflammation the cotton pellets granuloma method was employed. Formaldehyde induced arthritis was used as a model of chronic inflammation. Result: The acute inflammation produced by carrageenan, histamine and formaldehyde was significantly reduced by pretreatment with Ca++ channel blockers of di-hydropyridine group P<0.01 exception being Nimodipine which showed varied results. Similarly in sub-acute inflammation model of cotton pellet implantation the drugs showed significant inhibition of inflammation exception being Nimodipine which showed significant protection in high dose 40mg/kg oral P<0.01.In chronic arthritis induced by formaldehyde there was a dose dependent reduction in paw oedema varying from P<0.05 at 10mg/kg oral dose to P<0.01 at 40mg/kg dose. Conclusion: These findings suggest that CCBs exert significant dose dependent anti-inflammatory activity against acute, sub acute and chronic models of inflammations.